Research on Challenges in the Construction of University Teaching Staff — Taking Foreign Language Universities as an Example - Jing , Dong (Journal of Vasyl Stefanyk Precarpathian National University, 2025)
With the accelerated development of globalization, higher education in China in foreign languages is constantly undergoing innovative transformations. There are increasing demands for the cultivation of interdisciplinary talents in foreign languages. The shortage of specialized teaching staff, particularly high-level talents, is a critical issue that urgently needs to be addressed in developing and transforming foreign language universities. How to effectively structure the foreign language teaching staff, ensure the sustainable development of the teaching faculty, and strengthen the ideological and political development of the teaching staff are important challenges that must be resolved in the process of building a high-level university. The modern tendencies of teaching foreign languages in higher school are analyzed. Reforming the educational process in HEI according to the European standards is taken into consideration. The crucial objective of teaching foreign languages nowadays is the student’s communicative competence. Qualified language preparation is impossible without using innovative educational technologies. For this purpose, the programs of the teachers' continuing professional development ought to be designed to enhance their cross-cultural communication skills and global outlook. They can be achieved through international academic exchanges, foreign training, and joint research with international institutions. The modern methods of teaching foreign languages using innovative educational technologies are revealed. A more scientific and reasonable evaluation of teaching staff should be made, such as the teaching performance and research achievements, as well as the contribution to the development of an international perspective and abilities in cross-cultural communication. This will inspire enthusiasm among teachers to constantly improve and innovate their teaching activities and will, therefore, stimulate the general development of teaching staff in foreign language universities.